Personal factors associated with satisfaction with tutoring in engineering students - Palacios Garay, Jessica Paola (2021)
The tutoring of university students is very relevant for the achievement of engineering learning and personal factors are associated with satisfaction, establishing that the knowledge of these factors makes it possible to take measures that contribute to improve tutoring actions. The objective of the research was to establish the association of personal factors to satisfaction with tutoring in engineering students. A quantitative approach was chosen, the design was non-experimental and the association of personal factors with satisfaction with university tutoring. The population consisted of 800 engineering students and by means of probabilistic sampling with a 3% margin of error, the sample consisted of 458 students. The results showed that satisfaction with the university tutor is associated with the factors sex, age and college of origin, obtaining the Chi-square value x2 = 189.618a, 157.728a and 118.106a (p < 0.05); satisfaction with the university tutor associated with factors of sex, age and school of origin, obtained a Chi-square x2 = 189.618a, 157.728a and 118.106a (p < 0.05) and satisfaction with the organization and contents of the tutoring was associated with factors of sex, age and school of origin obtained a Chi-square x2 = 8.876a, 23.189a and 17.327a (p < 0.05). It is concluded that personal conditions are associated with satisfaction with tutoring, with the university tutor and with the organization and contents of tutoring in engineering students.